Implementasi Undang-Undang No 6 Tahun 2014 Pemerintahan Desa Dengan Menggunakan Konsep “Tigo Tungku Searangan” (Studi Kasus Sinergisitas Pemerintah Desa, Adat Dan Syarak Di Kabupaten Kampar Provinsi Riau) - Rustam, Afrinaldy (UIR PRESS, 2020)
The main problem in this study was how the social significance of the existence of Desa autonomy regulation through the Law No. 6 of 2014. The existence of new regulation must be influence to desa’s order, especially in local authority, Because of the local authority is the most important thing in local organization like Desa.The specific question tried to be answered in this study whether the Law could serve, integrate, and organize the local authority in Desa. The result of this research indicate three points. First, local authority existing that called “hak asal usul desa” coexist with local community and desa government. Second, the field of local authority as organization the governance of desa, implementation of the building of desa, and commmunity development will blossom out in the future depend on the needs of local community.Finally, design of local authority based on the Law No. 6 of 2014 can integrate and organize the local authority, if the national government still commit and consist to recognize the local authority whatever Desa has.